Faktor-faktor yang mempengaruhi kecemasan ibu hamil trimester III - Nurfaizah Alza; Ismarwati Ismarwati (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2017)
Abstract: The purpose of this study was to determine the factors thatinfluence on anxiety of pregnancy third trimester. This research is adescriptive cross-sectional design. The sampling technique used isconsecutive sampling with the total sample 61 respondents. The analysisused is independent t test. The results showed the factors that influenceon anxiety of pregnancy third trimester is the support of husband with ap value of 0,048 (p 0.05), while the age of mother, education level,occupation, gravidity and physical exercise can not be influence relatedto anxiety of pregnancy third trimester with p 0,05. Conclusions factorsthat influence anxiety third trimester pregnant women isthe support ofhusband.